2023
DOI: 10.57125/fed.2023.06.25.03
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of clip thinking in the context of digitalization of the educational environment of the future

Abstract: The article is devoted to the study of the use of clip-thinking technology in the educational process. The author analyzes the features of this method and offers recommendations for its effective use. In particular, the author emphasizes the importance of taking into account the age characteristics of students when using video materials, combining clip thinking with other teaching methods and tools, as well as the need to constantly update and maintain the library of video materials. Therefore, the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The study by Marathe (2018), in which the researcher identified the possibility of global digitalization of the educational space, is noteworthy. These results are also confirmed in the subsequent study by Khrenova et al (2023), who also noted the psychological features of working with modern students.…”
Section: Describe Relevant Scholarshipsupporting
confidence: 77%
“…The study by Marathe (2018), in which the researcher identified the possibility of global digitalization of the educational space, is noteworthy. These results are also confirmed in the subsequent study by Khrenova et al (2023), who also noted the psychological features of working with modern students.…”
Section: Describe Relevant Scholarshipsupporting
confidence: 77%